Human capital, technology intensity and growth in a regional context - Donata Favaro; Eniel Ninka; Margherita Turvani (European Regional Science Association (ERSA), 2010)
This paper contributes to the vast literature on the regional application of endogenous growth theory. A well known feature of capitalist growth and development is the vast and persistent divergence in per capita income growth between regions. These differences have been explained theoretically and empirically with neoclassical approaches emphasising increasing returns at regional level, with reference to the development of industrial district, for example, with the new interest in growth theory in connection with regional and urban growth processes. The new economics of urban and regional growth look at the 'local' dimension focalizing on the role of the so-called knowledge economy as an explanation for uneven development across regions. Within this heterogeneity, the operation of human capital and knowledge spillovers play their role in differentiating growth rates. The study of the concentration of specific mix of economic activities and human capital, with a 'fine grain' focus at the local level, is a useful tool to understand growth and spatial differentials. In this study we develop an empirical analysis of the pattern of growth in the Veneto region, focusing mainly on the role played by human capital employed in sectors with different technology intensities. To do so, we build up an original dataset by merging data available at very local level (Local Labour Systems-LLS), produced by the National Institute of Statistics, with our elaborations on data from an employee-employer dataset made available by the Local Labour Agency (Veneto Lavoro) and including all employment spells in the Veneto region. This dataset allows to define the human capital content of every worker and to classify firms accroding to their technology intensity. This dataset is used to estimate growth equations for the cross-section of the Venetian LLS and to test the validity of different growth models. In particular, we test the existence of a model √ la Romer (1990) considering the relative importance of human capitale working in high-medium/high-medium/low and low technology sectors (OECD classification). The results underline how growth in the Veneto region is positively affected by human capital employed not in the high-medium/high technology industries, but in medium and medium/low ones.
Keywords: 330